Pharmacological and non‐pharmacological strategies for obese women with subfertility - Taghavi, Seyed Abdolvahab (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effectiveness and safety of pharmacological and non‐pharmacological strategies compared with each other, placebo or no treatment, for obese women with subfertility.